Whiteness and leisure - Spracklen, Karl (Leisure Studies in A Global Era., 2013)
"The way in which leisure is used to construct whiteness and the way in which whiteness shapes leisure, is an important unanswered theme in sociological analyses of leisure. This book develops a new theory of instrumental whiteness and leisure, which draws in part on existing leisure theories and in part on the critical theorising around "race" and whiteness. In developing a new theory of whiteness and leisure, new primary and existing secondary empirical research is drawn upon to highlight whiteness across a comprehensive and internationally-grounded range of leisure practices. The book explores sports participation, sports media and sports fandom, informal leisure, outdoor leisure, music, popular culture and tourism. This book is grounded in Spracklen's development of leisure theory that uses a Habermasian framework of communicative and instrumental rationalities and actions to understand the tensions between utopian theories of individualized leisure and dystopian theories of increasing constraint and control. "--